PENGARUH PENGGUNAAN KANGKUNG (IPOMOEA AQUATIQA) UNTUK PERAWATAN KULIT KEPALA BERKETOMBE - Setiawati, Erlin; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The background of this study was the uncomfortable feelings un scalp at the time of performing activities. The study used water spinach to treat scalp with dry dandruff and aimed to analyze the effects of water spinach usage on the treatment of scalp with dry dandruff by observing removals of dandruff debris from scalp. The type of this study was quasi experimental with randomized control group pre-test post-test design. Subjects were female students wearing hijab with the same criteria. Samples were chosen using purposive sampling method, performed voluntarily on nine participants. The study consisted of three different groups, those are one control and two experimental groups. Data collected was primary data from samples, collected from prepared study forms. Data was analyzed using analysis of variance (Anova) followed with Duncan multiple comparison procedure. The result of this study showed significant difference among groups in dandruff debris removal from scalp.Keywords: Kangkung (Ipomoea aquatica), scalp dandruff.